Pengaruh Penggunaan Media Sosial Terhadap Kebiasaan Belajar Mahasiswa Program Studi Ekonomi Syariah UIN SMH Banten - Lilis Lilis; Nurul Farhah; Arini Jannati; Wahyu Hidayat; Hadi Peristiwo (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Social media has become an inseparable part of people's lives, including in the world of education. Students can use social media for various purposes, including to support the learning process. This research aims to understand how the use of social media by Islamic Economics students at UIN SMH Banten influences their study habits. The research method used is quantitative descriptive. Data was collected through questionnaires distributed to students to find out about the social media they use, duration of use, and purpose of use, as well as its influence on study habits. The research results show that social media has a positive and significant influence on student study habits. Simultaneously, the social media variable as a whole contributes 49.2% to the study habits variable.